Mengukir Masa Depan Bangsa: Pendidikan Pancasila Sebagai Upaya Memperkuat Karakter Generasi Muda Indonesia - Purnamasari, Yayang; Ridhwan, Andrea Syahla Nathaniela; Tsania, Aura Rizky; Putri, Azzahra Dwi Maulani; Nazwa, Fatimah An; Sundari, Marisa Ayu; Liandi, Nura Alisha; Handayani, Shinta Risma; Mufidah, Siti Rahma (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Pancasila Education as an Effort to Strengthen the Character of Indonesia's Young Generation Pancasila education is a compulsory subject at all levels of education in Indonesia. Today's younger generation has lost moral values and character. This study aims to determine the role of Pancasila education as an effort to strengthen the character of the younger generation. This research uses a qualitative approach through the literature review method. Data collection is carried out through secondary data sourced from scientific articles. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results of data analysis show that the younger generation needs to be repositioned in behaving by leaving the hedonic culture and outside culture that is not in accordance with the values of Pancasila. In addition, they must also actively ground Pancasila in community life. The active role of the younger generation, including students, in maintaining and implementing the values of Pancasila is key in carving out the future of the nation. Students as the frontline in struggle, renewal, and nation building are expected to be able to take advantage of the opportunity to forge themselves and learn to become individuals who have the character of nationalism, creativity, and the spirit of service to the community, nation, and state